Design and evaluation of vibratory shoe on balance control for elderly subjects: technical note. (17th February 2018) - Aboutorabi, Atefeh; Arazpour, Mokhtar; Farahmand, Farzam; Bahramizadeh, Mahmood; Fadayevatan, Reza; Abdollahi, Ehsan
Abstract: Background and Aim: Aging often results in a decline in somatosensory function, and such changes are associated with diminished motor performance. Input noise can enhance sensory and motor function through a mechanism known as stochastic resonance (SR). This paper describes the development and testing of a new vibrating shoe to possibly assist the elderly patients in controlling their balance and decreasing their falling risks. Technique: The new vibrating shoe was evaluated to ascertain its ability to generate appropriate random and nonlinear vibrations. The vibratory shoe performance in two young subjects with decreased foot sensation and two elderly subjects in different static and dynamic balance situations was also evaluated. The postural control, expressed by the stability index (SI), was significantly affected by SR in the older subjects. Discussion : The vibrating motors could be recommended as a suitable solution for dynamic balance situations. Moreover, the new vibrating shoe could improve the age-related balance impairments in elderly subjects with balance deficiencies and others with impaired foot sensations. Implications for rehabilitations: Older adults exhibited decreased postural stability. Noise signal improves sensation and proprioception in older people. New shoe with vibrating motors can operate in different dynamic situations.